Addition of four doses of rituximab to standard induction chemotherapy in adult patients with precursor B-cell acute lymphoblastic leukaemia (UKALL14): a phase 3, multicentre, randomised controlled trial. Issue 4 (April 2022) - Marks, David I; Kirkwood, Amy A; Rowntree, Clare J; Aguiar, Melanie; Bailey, Katharine E; Beaton, Brendan; Cahalin, Paul; Castleton, Anna Z; Clifton-Hadley, Laura; Copland, Mhairi; Goldstone, Anthony H; Kelly, Richard; et al.
Summary: Background: Treatment for adults with acute lymphoblastic leukaemia requires improvement. UKALL14 was a UK National Cancer Research Institute Adult ALL group study that aimed to determine the benefit of adding the anti-CD20 monoclonal antibody, rituximab, to the therapy of adults with de novo B-precursor acute lymphoblastic leukaemia. Methods: This was an investigator-initiated, phase 3, randomised controlled trial done in all UK National Health Service Centres treating patients with acute lymphoblastic leukaemia (65 centres). Patients were aged 25–65 years with de-novo BCR-ABL1 -negative acute lymphoblastic leukaemia. Patients with de-novo BCR-ABL1 -positive acute lymphoblastic leukaemia were eligible if they were aged 19–65 years. Participants were randomly assigned (1:1) to standard-of-care induction therapy or standard-of-care induction therapy plus four doses of intravenous rituximab (375 mg/m 2 on days 3, 10, 17, and 24). Randomisation used minimisation and was stratified by sex, age, and white blood cell count. No masking was used for patients, clinicians, or staff (including the trial statistician), although the central laboratory analysing minimal residual disease and CD20 was masked to treatment allocation. The primary endpoint was event-free survival in the intention-to-treat population. Safety was assessed in all participants who started trial treatment. This study is registered with ClincialTrials.gov, NCT01085617 . Findings: Between April 19, 2012, and July 10, 2017, 586 patients were randomly assigned to standard of care (n=292) or standard of care plus rituximab (n=294). Nine patients were excluded from the final analysis due to misdiagnosis (standard of care n=4, standard of care plus rituximab n=5). In the standard-of-care group, median age was 45 years (IQR 22–65), 159 (55%) of 292 participants were male, 128 (44%) were female, one (<1%) was intersex, and 143 (59%) of 244 participants had high-risk cytogenetics. In the standard-of-care plus rituximab group, median age was 46 years (IQR 23–65), 159 (55%) of 294 participants were male, 130 (45%) were female, and 140 (60%) of 235 participants had high-risk cytogenetics. After a median follow-up of 53·7 months (IQR 40·3–70·4), 3-year event-free survival was 43·7% (95% CI 37·8–49·5) for standard of care versus 51·4% (45·4–57·1) for standard of care plus rituximab (hazard ratio [HR] 0·85 [95% CI 0·69–1·06]; p=0·14). The most common adverse events were infections and cytopenias, with no difference between the groups in the rates of adverse events. There were 11 (4%) fatal (grade 5) events in induction phases 1 and 2 in the standard-of-care group and 13 (5%) events in the standard-of-care plus rituximab group). 3-year non-relapse mortality was 23·7% (95% CI 19·0–29·4) in the standard-of-care group versus 20·6% (16·2–25·9) in the standard-of-care plus rituximab group (HR 0·88 [95% CI 0·62–1·26]; p=0·49). Interpretation: Standard of care plus four doses of rituximab did not significantly improve event-free survival over standard of care. Rituximab is beneficial in acute lymphoblastic leukaemia but four doses during induction is likely to be insufficient. Funding: Cancer Research UK and Blood Cancer UK.